Role of Masjid in Social Reformation in Contemporary Pashtun Society: A Case Study of District Bannu and Lakki Marwat, Pakistan - Fida ur Rahman; Rashid Ahmed (Journal of Islamic and Religious Studies, 2018)
Pulpit and Masjid play very pivotal and productive role in a Muslim society. It not only educates and guides Muslims in religious matters as well shapes the social attitude and role of Muslims. Moreover, it is evident by the history that Islamic State was run by the Head of the State from Masjid. Unfortunately, pulpit and Masjid have been losing sense of their actual responsibility as an agent of social cohesion, integration and reformation. The paper is an attempt of studying the current role of pulpit and Masjid regarding religious education and training, exploring the factors that have been hampering the way of realizing the dream of social reformation in contemporary Pashtun society by not allowing pulpit and Masjid to play its due role in this respect and suggesting feasible recommendation for coping with the issue. The study is based on primary data that was collected through questionnaire in District Bannu and Lakki Marwat.